Reflectance and Thermal Micrometeorological Characteristics of an Urban Green Space in the Mediterranean During July’s 2023 Heatwave - Nikolaos D. Proutsos; Alexandra D. Solomou; Stefanos P. Stefanidis; Ioannis X. Tsiros (Land)
The thermal and optical behavior of different elements in the urban environment is critical for urban climate regulation and planning. This study investigates the micrometeorological conditions prevailing in an urban green space (UGS) in Greece, during the heatwave of July 2023, addressing the effects of various surface materials on thermal dynamics and the urban heat island (UHI) phenomenon. The research is based on ground surface temperature and albedo measurements on different materials in the UGS, in the morning and at noon, showing great temperature differences between the different types of materials. The findings highlight the complex interaction between high-albedo surfaces and surface temperature values, suggesting that the proper selection of materials can highly affect the optical and thermal behavior of the urban environment. Artificial materials absorb more heat compared to natural vegetation, leading to high surface temperature values, reaching at noon, for example, 58.9 °C for asphalt. For the natural surfaces, dry bare soil presents similar thermal behavior (64.1 °C at noon), while green surfaces had much lower temperatures (e.g., 38.3 °C for grass). Thermal comfort indices revealed that July 2023 experienced extensive “very hot” conditions, imposing the urgent need for strategic urban planning to mitigate heat impacts. The study highlights that in order to create climate-resilient environments and improve thermal comfort, it is crucial to include suitable materials and a variety of vegetation in urban design. Such insights into the complex nature of urban microclimate indicates also the issue of the careful selection of materials and plant species in urban greening initiatives to help cities face the UHI phenomenon.